Psychometric hepatic encephalopathy score (PHES) – when, how, why, and why not: a guide for the unfamiliar - Mumdzhiev, Nikola; Tenev, Rumen V.; Radicheva, Mariana P. (Gastroenterology Review/Przegląd Gastroenterologiczny, 2025)
Psychometric hepatic encephalopathy score (PHES) has established itself as one of the most used tests for detecting minimal hepatic encephalopathy. To use it in a certain population one needs to determine what the norms are, and have a proper set of inclusion and especially exclusion criteria. When performing the test (either for validating or as a search tool) authors may benefit from a little guidance. All the 5 tests – DST (Digital Symbol test), Number Connection Test A (NCT A), Number Connection Test B (NCT B), Serial Dotting Test (SDT), Line Drawing Test (LDT) – have certain parameters to follow. In time, deviations have appeared, and comparability between different samples has become somehow limited. As new tests are emerging, and in order to compare, one must be familiar with the tests’ variants, benefits, and limitations.